DAMPAK JUAL BELI ONLINE TERHADAP PASAR TRADISIONAL (Studi Kasus Pasar Kedungwuni): (Studi Kasus Pasar Kedungwuni) - novianti, imelda; Indah Purwanti; Versiandika Yudha Pratama (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
The rapid development of information technology today has resulted in major changes in various aspects, including production, sales and consumer markets. The purpose of this research is to investigate the impact of online buying and selling on traditional markets in Pekalongan and how they respond by analyzing traditional market traders' perspectives on online buying and selling and their responses to this change. The research results show that traditional traders have a high awareness of the increase in online sales, with 90% of them believing that online sales will continue to increase in the future. This indicates that traditional traders recognize the significant influence of online sales Regarding the response of traditional traders, the results of statistical analysis show that around 60% of them had a positive response. This positive response includes traders' awareness of competition with online sales, understanding of the advantages of buying and selling in traditional markets, and the weaknesses of online buying and selling. They are trying to come up with suitable strategies to compete in this changing environment and are even trying to enter the world of online sales. By considering traders' perceptions and responses that show adaptability, it can be concluded that in general, traditional traders are able to respond well to developments in online sales, so that they can survive in the era of information technology that continues to develop